Changes in Neck Muscle Thickness Due to Differences in Intermittent Cervical Traction Force Measured by Ultrasonography - Kuniyasu, Katsushi (The Society of Physical Therapy Science, 2014)
[Purpose] Many patients receive intermittent cervical traction in a daily treatment setting. However, unified settings for traction force, duration, and direction have yet to be determined. Therefore, an objective index is required to determine changes in traction conditions or to indicate its effectiveness. [Subjects] Fifteen healthy males volunteers participated in this study. [Methods] The thickness of the trapezius and splenius capitis muscles before and during traction were measured using ultrasonography at three traction forces: 5, 8 and 11 kg. [Results] Significant differences in muscle thickness were observed at 11 kg in the trapezius, and at 8 kg and 11 kg in the splenius capitis muscles. The muscle thickness ratio of the trapezius muscle showed a significant difference between 11 kg and 5 and 8 kg, and between 5 kg and 8 and 11 kg, as well as between 8 kg and 11 kg for the splenius capitis muscles. [Conclusion] Differences in muscle direction between the trapezius and splenius capitis muscles may account for the contrasting results obtained at the 8 kg traction force. This finding suggests that cervical traction must be performed considering the effects on different neck regions.